2019
DOI: 10.1021/acs.inorgchem.9b01340
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum-Catalyzed Ammonia Formation Using Simple Monodentate and Bidentate Phosphines as Auxiliary Ligands

Abstract: We have found molybdenum-catalyzed ammonia formation using simple and commercially available monodentate and bidentate phosphines as auxiliary ligands with a simple and convenient procedure. Molybdenum complexes generated in situ from [MoI3(THF)3] and the corresponding phosphines such as PMePh2 and 1,5-bis­(diphenylphosphino)­pentane worked effectively toward ammonia formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 64 publications
1
49
0
Order By: Relevance
“…On the other hand, Nishibayashi et al. recently showed that Chatt complexes with mono‐ and bidentate ligands indeed catalyse the generation of ammonia from N 2 if SmI 2 /H 2 O (or SmI 2 /alcohol) is used as reductant and proton source [20] . Using cis , mer ‐[Mo(NNH 2 )(OTf) 2 (PMePh 2 ) 3 ] as example for a NNH 2 intermediate also led to catalytic amounts of NH 3 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, Nishibayashi et al. recently showed that Chatt complexes with mono‐ and bidentate ligands indeed catalyse the generation of ammonia from N 2 if SmI 2 /H 2 O (or SmI 2 /alcohol) is used as reductant and proton source [20] . Using cis , mer ‐[Mo(NNH 2 )(OTf) 2 (PMePh 2 ) 3 ] as example for a NNH 2 intermediate also led to catalytic amounts of NH 3 .…”
Section: Methodsmentioning
confidence: 99%
“…To determine the N−H BDFE of the NNH‐intermediate for a given N 2 ‐reduction catalyst, DFT calculations may be employed [20] . Transfer of one electron and one proton to the Mo 0 ‐dinitrogen complex leads to the neutral Mo I ‐diazenido(−) intermediate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6] Quite recently, we developed a procedure for the catalytic formation of ammonia using a molybdenum trichloride complex bearing an N-heterocyclic carbene-and phosphine-based PCP-type pincer ligand [MoCl 3 (PCP)] 1[PCP = 1,3-bis(di-tert-butylphosphinomethyl)benzimidazol-2-ylidene], samarium diiodide (SmI 2 ) as a reductant and water as a proton source (Scheme 1). 7,8 In this reaction system, the amount of generated ammonia reached 4350 equivalents based on the molybdenum atom of the catalyst and the turnover frequency reached 113 equivalents of ammonia per minute based on the molybdenum atom of the catalyst. This effective and rapid reaction system for ammonia synthesis prompted us to investigate the reaction of atmospheric pressure of nitrogen gas with SmI 2 and water in the presence of 1 as the catalyst on a large scale.…”
mentioning
confidence: 92%